2017
DOI: 10.1038/sigtrans.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cellular pathways in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is a debilitating disease that is associated with poor prognosis, short median patient survival and a very limited response to therapies. GBM has a very complex pathogenesis that involves mutations and alterations of several key cellular pathways that are involved in cell proliferation, survival, migration and angiogenesis. Therefore, efforts that are directed toward better understanding of GBM pathogenesis are essential to the development of efficient therapies that provide hope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
252
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(263 citation statements)
references
References 146 publications
(164 reference statements)
5
252
0
6
Order By: Relevance
“…Treatment of cell line and xenograft with METex14 or ZM fusion with PLB-1001 resulted in MET signaling inhibition and reduced tumor volume. Despite several ongoing MET-targeting clinical trials in glioma (Pearson and Regad, 2017), our study highlights a precision neurooncology approach by identifying patients with MET alterations. In our phase I clinical trial, PLB-1001 monotherapy demonstrated a safety profile for patients with ZM fusion and/or METex14.…”
Section: Discussionmentioning
confidence: 92%
“…Treatment of cell line and xenograft with METex14 or ZM fusion with PLB-1001 resulted in MET signaling inhibition and reduced tumor volume. Despite several ongoing MET-targeting clinical trials in glioma (Pearson and Regad, 2017), our study highlights a precision neurooncology approach by identifying patients with MET alterations. In our phase I clinical trial, PLB-1001 monotherapy demonstrated a safety profile for patients with ZM fusion and/or METex14.…”
Section: Discussionmentioning
confidence: 92%
“…CQ and its derivative hydroxychloroquine (HCQ) are known inhibitors of autophagy, used in the clinics to treat GBM tumors, typically in combinatorial therapies together with the alkylating agent temozolomide (TMZ), and contribute, in some cases, to extend survival prognoses in patients affected by these aggressive, autophagy‐prone tumors . The N , N ‐(8‐hydroxyquinoline)methyl‐substituted benzylamine JLK1486 has been reported to inhibit cellular proliferation in B16F10 skin melanoma cells, via induction of cytodestructive autophagy .…”
Section: Introductionmentioning
confidence: 99%
“…PDGFR and TGF-β pathways are known to be dysregulated in GBM and they contribute to its pathogenesis and progression [64]. PDGFR and TGF-β are are currently considered as therapeutic targets [64,65].…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
“…PDGFR and TGF-β pathways are known to be dysregulated in GBM and they contribute to its pathogenesis and progression [64]. PDGFR and TGF-β are are currently considered as therapeutic targets [64,65]. In addition, TGF-β activity is associated with differences in prognosis in gliomas, including GBM [65,66].…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%